Morphology impact of the dike of the autonomous port of Kribi on the Cameroonian coast. (February 2022) - Jose Pako Perabi, Clotaire; Onguene, Raphael; Abessolo, Gregoire Ondoa; Ele, Pierre
Abstract: This paper presents an assessment of the impact of the Kribi autonomous port dike (Cameroon) on the morphological evolution of the coastaline. The methodological approach consisted in the diachronic analysis of shorelines positions extracted from Landsat 7/8 satellite image archives acquired between November 2003 and May 2020, i.e. a total of 8 images acquired before and after the construction of the dike. In addition, GPS surveys were conducted in the study area to recalibrate the satellite images. Atmospheric, radiometric and geometric corrections were performed on these images using ENVI 5.2 software. DSAS (digital Shoreline Analysis system) version 5.2, an extension of ESRI ArcGIS software, was used to digitize the shoreline and calculate their rate of change. The results obtained show that before the establishment of the port (2003–2012) we observe overall on 9.5 km of portion of the shorelines studied a stability on 64.39% of the coast; 24.14% is in accretion followed by some notches of erosion observed on 11.47% of the coast. The average speed of overall change of the shorelines is +0.34 ± 0.24 m/year. After the implementation of the port (2014–2020), accretion is observed on 26.42% of the shoreline located upstream of the transit and a permanent erosive trend downstream of the structure (dike) and located on 29.97% of the shoreline. The overall average speed of change of the shoreline is −1.90 ± 0.12 m/year. A prediction of the shorelines by the Kalman filter method estimates a maximum accretion of 20.4 m in upstream transit and a maximum retreat in downstream transit of 13.7 m in 2040, which could endanger the fishing camps of the village Nlende during episodes of high tides and cause the loss of habitats (residential areas and nesting beaches of marine turtles). Highlights: The dike of the autonomous port of Kribi (Cameroon) impacts the morphology of the coastline. The forecast of the shoreline given by 2040 by the method of Kalman filter of digital shoreline analysis system predicts a maximum recession downstream transit of 13.7 m.. Landsat 8/7 satellite imagery is a low cost solution to study the historical evolution of coastal morpho-dynamics.